The sanctuary as a means of organizing urban space: a case study of selected sanctuaries in Poland - Sołjan, Izabela (Turyzm/Tourism, 2012)
This paper attempts to show that a sanctuary can alter urban space. A sanctuary is a very special place because of its religious nature and attracts both pilgrims and tourists. The spatial structure of a sanctuary is determined largely by changes in the volume and nature of pilgrim ‘traffic’. Modern pilgrimage centres are becoming more open to visitors who wish to take part in the life of a sanctuary, even if this involves non-religious activities. The sanctuary's religious offering is supplemented with typical tourism attractions. The establishment of a sanctuary affects the development and spatial organization of a city in a variety of ways. Large sanctuaries favour the development of sanctuary service zones that cater for pilgrims. This is also true in Poland. There are, however, some large and midsize sanctuaries that have no additional facilities designed for pilgrims and this is almost always true of regional and national sanctuaries in Poland.